Shewanella algae-induced relapsing peritoneal dialysis-associated peritonitis: a case report - Tang, Jiawei; Luo, Nana; Zhang, Yiming; Wang, Chen (Frontiers in Medicine, 2025)
This article presents a case report of relapsing peritoneal dialysis-associated peritonitis caused by Shewanella algae. The patient has experienced relapsing peritonitis, accompanied by abdominal pain and cloudy peritoneal dialysis fluid. Ascites culture revealed an infection with Shewanella algae. Treatment with high-concentration gentamicin sulfate via intra-catheter antibiotic instillation led to complete resolution of the infection, with no recurrence observed. Shewanella algae-induced peritoneal dialysis-related peritonitis is rare, and its relapsing nature may be attributed to bacterial biofilm formation within the catheter. High-concentration antibiotic lock therapy demonstrated efficacy in eradicating the infection. This report explores the efficacy and application value of antibiotic lock therapy in managing relapsing Shewanella algae-associated peritoneal dialysis-related peritonitis.